An adapted framework of Community of Inquiry (COI) framework for the development of blended learning / Nani Amalina Zulkanain - Zulkanain, Nani Amalina (2016)
This research is about to enhance the Community of Inquiry (COI) framework that includes the relationship of students’ perceptions and instructor involvement of SecondLife on blended learning approach for the development of blended learning platform. Blended learning is the combination of physical class and online class. Study show that most of the blended learning are conducted without the presence of instructor. In addition, it is hard for new educator to adapt in blended learning environment. This research will be focus on instructors’ involvement to produce a valuable educational experience. An experiment was conducted to observe the comparison of learning session by the involvement of the instructor and without instructor. The experiment shows agreement towards instructor involvement. Several guidelines for the development of blended learning system are founded based on the lesson learned from the observation of the experiment conducted. This new instructor presence element and guideline for blended learning system will be a platform to refer by developer and instructors as well as educators in order to enhance students’ performance, produce better learning outcome and provide ease of use. Since this research tends to use virtual world platform to analyse students’ perception because of the sense of presence provided by this platform, it will be better if this studies extended the potential the use of virtual world in blended learning compared to the portal-based platform. Next, further study is needed to investigate the role and responsibilities of the instructors’ teaching in blended learning. This will be a benefit to instructor in easily managing the students. Lastly, enhanced COI framework should be tested with larger sample size of respondent to indicate a successful framework to be used in blended learning.